Influence of Fluids on Earthquakes Based on Numerical Modeling. Issue 2 (21st February 2023) - Marguin, Valentin; Simpson, Guy
Abstract: The strength and sliding behavior of faults in the crust is largely controlled by friction and effective stress, which is itself modulated by fluid pressure. Most earthquake models assume a fixed pore fluid pressure despite widespread evidence that is varies strongly in time due to changes in permeability. Here we explore how dynamic changes in pore pressure influence the properties of earthquakes in the upper crust. To study this problem we develop a two dimensional model that incorporates slow tectonic loading and fluid pressure generation during the interseismic period with frictional sliding on a thrust fault whose permeability evolves with slip. We find that the presence of relatively modest fluid overpressures tends to reduce coseismic slip, stress drop, maximum sliding velocity, rupture velocity and the earthquake recurrence time compared to models without fluids. Our model produces a wide range of sliding velocities from rapid to slow earthquakes, which occur due to the presence of high pore pressures prior to rupture. The models also show evidence for aftershocks that are driven by fluid transfer along the fault plane after the mainshock. Overall, this study shows that fluids can exert an important influence on earthquakes in the crust, which is mostly due to modulation of the effective stress and variations in permeability, and to a lesser extent to poro‐elastic coupling. Plain Language Summary: In this study we use a numerical model to investigate how fluid pressures vary over the seismic cycle and how they interact with and influence the properties of earthquakes that occur in the upper crust. In the model, fluid overpressures are generated slowly during the interseismic period by phenomena such as dehydration reactions while they are episodically released during earthquakes due to fracturing and a dramatic increase in permeability. The models show that the presence of high fluid pressures has an important influence on earthquakes. High fluid pressures favor smaller, more frequent earthquakes. Also high fluid pressures may sometimes be responsible for aftershocks and for anomalously slow earthquakes that involve slip over several months rather than several seconds. Overall, we show that the presence of fluids in the crust plays an integral part in the earthquake process. Key Points: Properties of earthquakes are markedly influenced by the presence of fluid overpressures Ruptures in wet models have relatively low stress drops, sliding speed and rupture velocity Slow slip events and aftershocks might be a fingerprint of fluid overpressures